Sexually transmitted diseases knowledge assessment and associated factors among university students in the United Arab Emirates: a cross-sectional study - Alshemeili, Abdulla; Alhammadi, Ahmed; Alhammadi, Abdulrahman; Al Ali, Mohamed; Alameeri, Eisa Saud; Abdullahi, Aminu S.; Abu-Hamada, Bayan; Sheek-Hussein, Mohamud M.; Al-Rifai, Rami H.; Elbarazi, Iffat (Frontiers in Public Health, 2023)
Background: Sexually transmitted diseases and infections (STDIs) remain a serious public health menace with over 350 million cases each year. Poor knowledge of STDIs has been identified as one of the bottlenecks in their control and prevention. Hence, assessment of knowledge, both general and domain-specific, is key to the prevention and control of these diseases. This study assessed the knowledge of STDIs and identified factors associated with STDI knowledge among university students in the United Arab Emirates (UAE).Methods: This is a cross-sectional study among 778 UAE University students across all colleges. An online data collection tool was used to collect data regarding the participants' demographics and their level of knowledge of STDIs across different domains including general STDI pathogens knowledge (8 items), signs and symptoms (9 items), mode of transmission (5 items), and prevention (5 items). Knowledge was presented both as absolute and percentage scores. Differences in STDI knowledge were statistically assessed using Mann-Whitney U and Chi-squared tests. Logistic regression models were further used to identify factors associated with STDI knowledge.Results: A total of 778 students participated in the study with a median age of 21 years (IQR=19, 23). The overall median STDI knowledge score of the participants was 7 (out of 27), with some differences within STDI domainssigns & symptoms (1 out of 9), modes of transmission (2 out of 5), general STDI pathogens (2 out of 8), and prevention (1 out of 5).Higher STDI knowledge was significantly associated with being non-Emirati (OR=1.85, 95% CI=1.24-2.75), being married (OR=2.89, 95% CI=1.50-5.56), residing in emirates other than Abu Dhabi (OR=1.61, 95% CI=1.16-2.25), and being a student of health sciences (OR=4.45, 95% CI=3.07-6.45).In general, STDI knowledge was low among the students. Having good knowledge of STDIs is essential for their prevention and control. Therefore, there is a need for informed interventions to address the knowledge gap among students, youths, and the general population at large.